Diagnostic Accuracy of Ultrasonography for Diagnosing Liver Mass Taking CT Triphasic Liver as Gold Standard - Khalid, Abeer; Khan, Shamrez; Mushtaq, Adeebah; Khalid, Urwah; Khalid, Zainab; Shaheen, Ojala (Indus Journal of Bioscience Research, 2025)
Background: Accurate distinction of benign and malignant lesions of the liver is critical for a proper clinical management. Ultrasonography is first line imaging modality that is used for hepatic lesions; however, diagnostic accuracy of ultrasound is much improved when shear wave elastography (SWE) technique is employed for the characterization of liver lesion on the basis of tissue stiffness. This study was done to ascertain the diagnostic accuracy of ultrasonography with shear wave elastography in the diagnosis of liver masses using triphasic computed tomography (CT) as the reference standard. Methods: This cross-sectional validation study carried out at Radiology Department of Islamabad Diagnostic Centre, Islamabad during 22 June 2024 to 30th December 2024. A total of 208 patients between 25 and 75 years of age with suspected focal lesions in the liver were included. All patients were scanned with ultrasonography with SWE followed by triphasic CT of the liver. Demographic data, clinical features, and findings of the imaging studies were recorded. The performance parameters of the diagnostic test such as sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy were calculated using triphasic CT as a gold standard. Receiver operating characteristic (ROC) curve analysis was done to determine discriminative capacity of SWE stiffness values. Results: Triphasic CT identified malignant lesions in 152 (73.1%) patients and benign lesions in 56 (26.9%) patients. Ultrasonography with SWE correctly identified 128 true positive, 45 true negative, 11 false positive, and 24 false negative cases. The sensitivity, specificity, PPV, and NPV of ultrasonography with SWE were 84.2%, 80.4%, 92.1%, and 65.2%, respectively, with an overall diagnostic accuracy of 83.2%. ROC analysis demonstrated excellent diagnostic performance with an area under the curve (AUC) of 0.956 (95% CI: 0.931–0.980, p < 0.001). Conclusion: Ultrasonography when conducted with the use of shear wave elastography technique, reproduce high diagnostic accuracy in the discrimination of malignant and benign liver lesions. SWE provides useful quantitative information that adds to the diagnostic capability of conventional ultrasound and may prove a useful non-invasive adjunctive test in the evaluation of focal hepatic lesions.